Implementation of cervical cancer prevention services for HIV-infected women in Zambia: measuring program effectiveness. Issue 6 (November 2010) - Parham, Groesbeck P; Mwanahamuntu, Mulindi H; Sahasrabuddhe, Vikrant V; Westfall, Andrew O; King, Kristin E; Chibwesha, Carla; Pfaendler, Krista S; Mkumba, Gracilia; Mudenda, Victor; Kapambwe, Sharon; Vermund, Sten H; Hicks, Michael L; et al.
Background: Cervical cancer kills more women in low-income nations than any other malignancy. A variety of research and demonstration efforts have proven the efficacy and effectiveness of low-cost cervical cancer prevention methods but none in routine program implementation settings of the developing world, particularly in HIV-infected women.Methods: In our public sector cervical cancer prevention program in Zambia, nurses conduct screening using visual inspection with acetic acid aided by digital cervicography. Women with visible lesions are offered same-visit cryotherapy or referred for histologic evaluation and clinical management. We analyzed clinical outcomes and modeled program effectiveness among HIV-infected women by estimating the total number of cervical cancer deaths prevented through screening and treatment.Results: Between 2006 and 2008, 6572 HIV-infected women were screened, 53.6% (3523) had visible lesions, 58.5% (2062) were eligible for cryotherapy and 41.5% (1461) were referred for histologic evaluation. A total of 75% (1095 out of 1462) of patients who were referred for evaluation complied. Pathology results from 65% (715 out of 1095) of women revealed benign abnormalities in 21% (151), cervical intraepithelial neoplasia (CIN) I in 30% (214), CIN 2/3 in 33% (235) and invasive cervical cancer in 16.1% (115, of which 69% were early stage). Using a conditional probability model, we estimated that our program prevented 142 cervical cancer deaths (high/low range: 238–96) among the 6572 HIV-infected women screened, or one cervical cancer death prevented per 46 (corresponding range: 28–68) HIV-infected women screened.Conclusion: Our prevention efforts using setting-appropriate human resources and technology have reduced morbidity and mortality from cervical cancer among HIV-infected women in Zambia. Financial support for implementing cervical cancer prevention programs integrated within HIV/AIDS care programs is warranted. Our prevention model can serve as the implementation platform for future low-cost HPV-based screening methods, and our results mayprovide the basis for comparison of programmatic effectiveness of future prevention efforts.